PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PDAM KABUPATEN BONDOWOSO DENGAN KOMPENSASI SEBAGAI VARIABEL INTERVENING - Fahlezzi, Teguh Umar; Arief, Mohammad Yahya; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The aim of this study is to examine how the factors of Motivation and Work Environment impact Employee Performance within the Regional Water Supply Company (PDAM) of Bondowoso Regency, with compensation acting as an intervening variable. This analysis was conducted through the application of the Partial Least Square (PLS) structural equation model. The results of hypothesis testing using the Smart PLS 3.0 application indicate that motivation has a significantly positive effect on compensation (H1 accepted), the work environment has a significantly positive effect on compensation (H2 accepted), motivation has a positive but not significant effect on employee performance (H3 rejected), the work environment has a significantly positive effect on employee performance (H4 accepted), compensation has a significantly positive effect on employee performance (H5 accepted), motivation has a significantly positive effect on employee performance through compensation (H6 accepted), and the work environment has a significantly positive effect on employee performance through compensation (H7 accepted).